Haematological manifestations of HIV infected and HIV exposed Infants at Harare Central Hospital, Zimbabwe. - F,, Chimhundu; G, Chimhini; V,, Chikwasha; A, Mandisodza (IJRDO -JOURNAL OF HEALTH SCIENCES AND NURSING, 2017)
Background: Prevention of mother to child transmission (PMTCT) programs have resulted in increased numbers of HIV exposed uninfected infants. However, these infants have higher morbidity and mortality rates like their HIV infected counterparts. Exposure to the maternal HIV infection or antiretroviral drugs in the uterus and by neonatal prophylaxis is thought to have an impact on the haematology of these infants. The aim of the study was to compare the haematological manifestations of HIV exposed uninfected infants with those of HIV infected infants as both groups are born to HIV positive mothers. Methods: This was a prospective clinical and laboratory cross sectional study carried out at Harare Central Hospital in Zimbabwe from January to April 2017. Full blood counts were done on blood samples collected from HIV exposed uninfected and HIV infected infants between the age of 6 weeks and 2 years. Results were statistically analysed using SPSS version 20. Results: A total of 150 infants were recruited into the study. Forty-one (27.3%) were HIV infected and 109 (72.7) were HIV exposed uninfected. Anaemia was the most common abnormality in both HIV infected (80.5%) and HIV exposed uninfected infants (75.6%).The most common type was microcytic hypochromic anaemia in HIV exposed uninfected infants and normocytic hypochromic anaemia in HIV infected infants. Leukopaenia, neutropaenia and thrombocytopaenia were 9.2% and 2.4%, 16.5% and 19.5% and 7.3% and 20% in HIV exposed uninfected and HIV infected infants respectively. Thrombocytosis was present in HIV exposed uninfected infants. Conclusion: Abnormal haematological manifestations in HIV exposed uninfected infants were comparable to those of HIV infected infants. Anaemia was the common abnormality in the two groups of infants.